The Impact of Employees’ Perceived Business Ethics and Ethical Climate on Organizational Social Capital - (:unkn) unknown (My University, 2017)
0

In this study, the authors have attempted to investigate the impacts of ethical context on social capital through the perspectives of educational staff working in public and private educational institutions. The research model was tested using survey data collected from educational staff members in various in various primary and secondary educational institutions. A micro-level analysis was performed utilizing a structured questionnaire following the convenience sampling method. From the extant literature, ethical context, defined as the set of ethical climate and business ethics perceived by individuals arise as meaningful contextual attributes which affecting organizational social capital. In this study, the authors have operationalized ethical climate by measuring how employees perceive caring, law code, rules, instrumental, and independence dimensions of ethical climate as adopted from Victor and Cullen’s typology. To measure business ethics, the scale Perceived Organizational Ethical Values developed by Hunt, Wood, and Chonko was used. Finally, the dependent variable of the research model was measured using Nahapiet and Ghoshal’s Internal Social Capital Scale which measuring three dimensions of social capital. It was assumed that the level of perceived ethical climate and business ethics as being the contextual variables would make significant contributions to perceived organizational social capital. Findings from this research indicated that business ethics and ethical climate were both significantly and positively related with social capital, and furthermore, business ethics and ethical climate had a significant positive impact on social capital. According to these results, business ethics and ethical climate perceptions of the educational staff members are the important predictors of perceived social capital in Turkish educational institutions
Keywords: Tarih